Nilai-Nilai Kesehatan Pada Hadis Tentang Memendekkan Kumis Dan Memelihara Janggut: Health Values In The Hadith About Shortening The Mustache And Maintaining A Beard - Nurmala Sari; Muhammad Roihan Nasution (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2022)
The culture of keeping beards existed even before Islam came. Later in the prophetic period, the Prophet ordered Muslim men to shorten their mustaches and keep beards to contrast the customs of the Magi. Scholars have different views on the hadith of the Prophet, some understand it textually such as Nasir Al-Din Al-Albani, Abu Muhammad bin Hazm, Abdul Aziz bin Baz and some understand it contextually, such as Al-Syarbasi, Al-Qaradawi, and Shuhudi Ismail. For those who understand the hadith textually to this day, they shorten their mustaches and keep their beards. Some scientists conduct research on mustache and beard from a health perspective. The author conducted research with the aim of presenting health wisdom in hadith using qualitative research methods that are emphasized in literature review analysis. The author researched and analyzed the hadiths about mustache and beard through a health approach, it turned out that the two supported each other and showed a correlation. So, it can be concluded that shaving a mustache and maintaining a beard is Islamic law that has a fairly important influence in terms of health.